Al-Ma‘had al-Turāthī wa Taqwim al-Jamā‘ah: Tajribah Ma‘had Hidayatullah - Sirojudin Abbas (Studia Islamika, 1998)
This article discusses some of the characteristic peculiarities of the pesantren as in Pesantren Hidayatullah, Balikpapan, East Kalimantan, which does not make Arabic reviewing activities as part of the daily staple of his students.During the last three decades, pesantren in Indonesia have shown  a variety of institutional developments. The identification of pesantren as Islamic learning institutions-especially in term of their specific role in preserving intellectual tradition and reproducing 'ilama' may no longer be sufficient to explaint that development. Such a trend can be seen in the establishment of a significant number of Islamic learning institution in the country with different visions and characteristics of learning. One of the leading institutions representing this new form of pesantren is Pesantren Hidayatullah, Balikpapan, East Kalimantan.DOI: 10.15408/sdi.v5i2.756